Decreased fetal movements: Perinatal and long-term neurological outcomes. (October 2019) - Zamstein, Omri; Wainstock, Tamar; Sheiner, Eyal
Abstract: Background: While maternal perception of decreased fetal movements during advanced stages of pregnancy may be an indicator for adverse perinatal outcome, the long-term neurological outcome of offspring of affected pregnancies remains largely unknown. Objective: To examine whether maternal complaint of decreased fetal movements is associated with adverse perinatal outcomes, and to assess the implications of decreased fetal movements on long-term neurological morbidity of the offspring. Study design: A single center cohort analysis including deliveries between the years 1991–2014 was conducted. The association between decreased fetal movements and adverse perinatal outcome was evaluated using a general estimation equation (GEE) multivariable analyses. Incidence of hospitalizations (up to age 18 years) due to various neurological conditions was compared between offspring of affected pregnancies, and those who were not, using a Kaplan-Meyer survival curve. A Cox proportional hazards model was used to control for confounders. Results: 439 (0.18%) of 242, 342 deliveries included in this study were accompanied by maternal complaint of decreased fetal movements. Perinatal outcome was comparable between the groups, with no cases of perinatal mortality observed among the exposed group. Total neurological-related hospitalization rate of the offspring, as well as hospitalizations due to movement disorders, were higher among the exposed group (Kaplan-Meyer log-rank test P < 0.05). This association between decreased fetal movements and increased long-term neurological hospitalization proved to be independent of potential confounders with an adjusted hazard ratio of 1.54 (95% CI 1.0–2.37). Conclusion: Maternal complaint of decreased fetal movements does not predict adverse perinatal outcome but is associated with an elevated risk for long-term neurological morbidity of the offspring.